COVID-19 infection triggering Thrombotic Thrombocytopenic Purpura. (2021) - Alhomoud, Mohammad; Alhobayb, Tamara; Armitage, Keith
Abstract: We present a 62-year-old gentleman with history of Crohn's disease, G6PD deficiency, who presented with immune-mediated thrombotic thrombocytopenia purpura (iTTP) one week after the diagnosis of COVID-19 infection. He was admitted with worsening dyspnea, acute renal failure, and profound thrombocytopenia with marked schistocytosis on peripheral smear. ADAMTS13 level was severely deficient. He was treated with oral prednisone, plasma exchange and rituximab with complete clinical resolution. Given the temporal association of this recurrent episode of iTTP with COVID-19 infection and no other discernible cause, COVID-19 infection was the most likely trigger.